Ecology of the integron gene cassette metagenome - Timothy M. Ghaly (2018)
Integrons are genetic elements that promote rapid adaptation in bacteria by capturing exogenous mobile gene cassettes. Recently, a sub-set of gene cassettes have facilitated the global spread of antibiotic resistance, however, outside of clinical settings, very little is known about the function and ecology of these cassettes. Here, I sequenced whole cassettes from soils sampled across Australia and Antarctica, and recovered 44,970 cassettes that encoded 27,215 unique proteins. This represents an order of magnitude more cassettes than previous sequencing efforts. Cassettes had extremely high local richness, with estimates ranging from 4,000 to 18,000 unique cassettes per 0.3 grams of soil. Gene cassettes exhibited a rapid spatial turnover and had a heterogeneous distribution across space. More than 84% encoded unknown proteins, 64% of which had no homologs in existing databases. These findings provide insights into gene cassette ecology, and highlight the diversity in this metagenome. This diversity can generate genomic complexity and drive bacterial evolution. I also explore the potential use of integron gene cassettes in accelerating the discovery of novel proteins. The gene cassette metagenome represents a huge untapped resource that provides an efficient means to shed light on the dark matter of the protein universe. This resource is thus of substantial biotechnological importance, particularly for developing small-molecule therapeutics and engineering molecular tools.